PERANCANGAN SISTEM INFORMASI WORK ORDERDENGAN METODE ITERATIF MENGGUNAKAN FRAMEWORK CODEIGNITER (Studi Kasus :CV Sirna Miskin Bandung) - Abdussalaam, Falaah; Mardiansyah Ramadhan, Miftah (Politeknik Dharma Patria Kebumen, 2019)
This research was aimed to know the current of Work Order Information System at CV Sirna Miskin Bandung, to find out the problems facing, and to know how to cope these problems. Based on the research result, it turns out that the problems of work order data processing is still manual by using Spreadsheet application, so that the detail information of work order such as status, work duration, who’s working on it and report processing became slower and less accurate.To resolve these problems, it is neccessary work order information system design with an integrated database was needed for simplify the process of managing data, so that the information needed an report processing became faster, complete and precise.Data collection methods was using observation, interview and literature study, while the method of this information system design was using object oriented method with the UML (Unified Modelling Language) and implemented using framework PHP Codeigniter and MySQL as database. Iteration method was used as for the software development.The suggestion given is : 1) Perform maintenance, develop, and update to the system which designed sustainably, 2) Developing system to becomes larger by including other business process, 3) Create system for mobile version to improve accessibilty.